Formation of Organizational Identity: Analysis of Foreign Experience ("Journal "U". Economy. Management. Finance.", 2022)
In the article are considered the experience of foreign countries in the formation of organizational identity. The experience and personnel management in Japan, the USA, the UK, Italy, China and Korea are being studied. An assumption is put forward about the formation of organizational identity approaches in connection with geographical location. Based on the data, the conclusion is formulated that, depending on the cultures, either collectivism or individualism prevails.
Keywords: identity; organizational identity; analysis; experience; collectivism; individualism; identification